Prophylactic angiographic embolisation after endoscopic control of bleeding to high-risk peptic ulcers: a randomised controlled trial. Issue 5 (25th May 2018) - Lau, James Y W; Pittayanon, Rapat; Wong, Ka-Tak; Pinjaroen, Nutcha; Chiu, Philip Wai Yan; Rerknimitr, Rungsun; Holster, Ingrid Lisanne; Kuipers, Ernst J; Wu, Kai-Chun; Au, Kim W L; Chan, Francis K L; Sung, Joseph J Y
Abstract : Objectives: In the management of patients with bleeding peptic ulcers, recurrent bleeding is associated with high mortality. We investigated if added angiographic embolisation after endoscopic haemostasis to high-risk ulcers could reduce recurrent bleeding. Design: After endoscopic haemostasis to their bleeding gastroduodenal ulcers, we randomised patients with at least one of these criteria (ulcers≥20 mm in size, spurting bleeding, hypotensive shock or haemoglobin<9 g/dL) to receive added angiographic embolisation or standard treatment. Our primary endpoint was recurrent bleeding within 30 days. Results: Between January 2010 and July 2014, 241 patients were randomised (added angiographic embolisation n=118, standard treatment n=123); 22 of 118 patients (18.6%) randomised to angiography did not receive embolisation. In an intention-to-treat analysis, 12 (10.2%) in the embolisation and 14 (11.4%) in the standard treatment group reached the primary endpoint (HR 1.14, 95% CI 0.53 to 2.46; p=0.745). The rate of reinterventions (13 vs 17; p=0.510) and deaths (3 vs 5, p=0.519) were similar. In a per-protocol analysis, 6 of 96 (6.2%) rebled after embolisation compared with 14 of 123 (11.4%) in the standard treatment group (HR 1.89, 95% CI 0.73 to 4.92; p=0.192). None of 96 patients died after embolisation compared with 5 (4.1%) deaths in the standard treatment group (p=0.108). In a posthoc analysis, embolisation reduced recurrent bleeding only in patients with ulcers≥15 mm in size (2 (4.5%) vs 12 (23.1%); p=0.027). Conclusions: After endoscopic haemostasis, added embolisation does not reduce recurrent bleeding. Trial registration number: NCT01142180 .